Die Seilbrücke bei Penipe – ein neuer Quellenfund zur Geschichte eines Bildes - Götz, Carmen (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2025)
A note written by Alexander von Humboldt has recently been discovered in the archives of the Knoblauchhaus Museum in Berlin. The subject of the note, written in French, is the rope bridge at Penipe (in present-day Ecuador), which Humboldt and Bonpland crossed on 18 June 1802 on their journey through the American tropics and which is depicted in a picturesque illustration in the monumental atlas Vues des Cordillères.The article provides a transcription of the manuscript, together with a commentary and a translation into German. It also compares the note with the original sources (American travel journal, Vues des Cordillères). The article also attempts to clarify questions of dating, possible addressees, and possible context of use. Finally, the author considers how this note might have found its way into the extensive collection of the Knoblauch family estate.